Integrated multi-omics, spatial profiling and organoid modeling drive transformative advances in chronic liver disease and hepatocellular carcinoma immunomicroenvironment research - Liu, Qi; Wang, Chenyu; Ye, Cheng; Zhang, Huawei; Li, Teng; Wei, Wenjuan; Wang, Senyan; Zhang, Huapeng (Frontiers in Immunology, 2026)
Chronic liver disease (CLD) represents a major global public health challenge, necessitating a systematic understanding of its complex immunopathological mechanisms. This review comprehensively summarizes the groundbreaking applications of cutting-edge technologies—including single-cell sequencing, spatial transcriptomics, and organoid models—in chronic liver disease immunology research: Single-cell sequencing resolves immune cell heterogeneity at unprecedented resolution, identifies rare cell subsets, and reveals dynamic changes and regulatory networks through multi-omics integration; Spatial transcriptomics complements this by mapping immune-stromal interactions within structural contexts such as the portal tract, fibrotic septa, and tumor niches, uncovering spatially organized immune evasion mechanisms and microenvironmental remodeling; Organoid technology constructs humanized liver-immune models that recapitulate disease-specific features—such as fibrosis, steatohepatitis, and hepatocellular carcinoma—enabling mechanistic validation, drug screening, and individualized therapeutic exploration. The synergistic integration of multi-omics profiling, spatial mapping, and organoid modeling is driving a paradigm shift in chronic liver disease immunology—transitioning from static cellular descriptions to spatiotemporal mechanism decoding, and from population-level insights to individualized pathophysiology and treatment prediction. These advanced approaches establish a technological foundation for building precision immunotherapeutic strategies tailored to spatiotemporal regulation of the liver immune microenvironment.